Ethnicity and Matriarchal Protest: A Case of Dialoguing Shona Personal Names - Livingstone Makondo (Names, 2008)
Abstract This paper examines the role of Zimbabwean (Shona) women in the naming of children in the patriarchal Shona society. The corpus of two thousand Shona personal/given names under review was gathered from Zimbabwe's seven predominantly Shona-speaking provinces. The discussion closely examines fifty-two personal names. It emerges that Zimbabwean (Shona) women are innovative as they manage to devise personal names that denotatively and connotatively put across their wishes, grievances, experiences, and preferences in acceptable and non-confrontational ways. The use of value-laden, palimpsest and emblematic-dialoguing personal names is a restrained strategy that ensures tranquility in the society. As a result, the name bearers become moving emblems of the frozen experiences and hopes of their mothers who might have directly or indirectly given the resultant name. In addition, a deconstructionist theory is promulgated as one of the means to get at the deeper meanings of the given names.